Baicalin Induces Apoptosis and Suppresses the Cell Cycle Progression of Lung Cancer Cells Through Downregulating Akt/mTOR Signaling Pathway - Sui, Xinbing; Han, Xuemeng; Chen, Peng; Wu, Qibiao; Feng, Jiao; Duan, Ting; Chen, Xiaying; Pan, Ting; Yan, Lili; Jin, Ting; Xiang, Yu; Gao, Quan; et al. (Frontiers in Molecular Biosciences, 2021)
Baicalin as a natural active ingredient extracted and isolated from the traditional Chinese medicine Scutellaria baicalensis Georgi., which has been potentially used in various area for its anti-oxidative, anti-tumor, anti-inflammatory and anti-proliferative activities. Although several studies have reported the anti-tumor effects of baicalin against various cancer types, however, its beneficial effects on lung cancer have not yet been elucidated. Therefore, the therapeutic effects and molecular mechanisms of baicalin on lung cancer cell lines H1299 and H1650 were investigated. Here, the results of its anti-tumor activity were shown. We found that Akt/mTOR pathway inhibition was the essential determinant in baicalin-induced cell cycle arrest. Furthermore, when the Akt Agonist SC79 or Akt plasmid transfection was performed, the anti-tumor effect of baicalin was significantly abrogated in both H1299 and H1650 cells. In conclusion, we found that the baicalin exerted its anti-tumor activity mainly by inducing Akt-dependent cell cycle arrest and promoting apoptosis